Negative Effects of the Neonicotinoid Clothianidin on Foraging Behavior and Antennal Sensitivity in Two Common Pollinator Species, Osmia bicornis and Bombus terrestris - Straub, Florian; Orih, Ihotu Joy; Kimmich, Judith; Ayasse, Manfred (Frontiers in Ecology and Evolution, 2021)
Insect species richness and abundance has declined rapidly over the last few decades. Various stressors, such as the conversion of natural habitats, climate change, land-use intensification, agrochemicals and pathogens, are thought to be major factors in this decline. We treated female bees of two common pollinator species in Europe, Osmia bicornis and Bombus terrestris, with a field-realistic dose of the neonicotinoid clothianidin. We tested its effects on the foraging behaviour of O. bicornis under semi-natural conditions and on the antennal sensitivity of both bee species to common floral volatiles by using electroantennography. Clothianidin negatively affected the foraging behaviour in O. bicornis by decreasing the number of flowers visited per foraging flight and by increasing the time per flower visit and the searching time between two flowers. It also decreased the antennal sensitivity of 2-phenylethanol-sensitive receptors in the two bee species. Thus, clothianidin is clearly a threat for bees via its effects on their foraging behaviour and antennal sensitivity and is hence probably detrimental for pollination and the reproductive success of bees.